Studi Mikroskopis Pada Batuan Metamorf (Schist) Daerah Ulunggolaka, Kabupaten Kolaka, Provinsi Sulawesi Tenggara - Aris, Ayub Pratama; Kobi, Wiwin (Journal of Applied Geoscience and Engineering, 2022)
Geographically, the observation area is included in Ulunggolaka Village, Latambaga District, Kolaka Regency, Southeast Sulawesi Province. This observation was conducted to determine the paragenesis of the formation of minerals in metamorphic rocks (Schist). The observation method is laboratory analysis (petrographic and mineragraphic analysis). The results of laboratory analysis observations on polished incisions are that there are intergrowth and replacement textures observed between pyrites, sphalerite and chalcopyrite minerals. Paragenesis in the observed samples is that in stage one pyrites are formed and in stage two pyrites and chalcopyrite grow together (intergrowth) and in stage three chalcopyrite is present replacing pyrites and in the last stage sphalerite mineralization is present replacing pyrites. Ore minerals that develop in the observation area are dominated by pyrite and chalcopyrite minerals according to the mineral deposit model included in the low sulfide epithermal deposit type.